2002
DOI: 10.2113/0320414
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Interactions of Foraminifera: Implications for Food Degradation and Bioturbation Processes

Abstract: Despite their small size, foraminifera often reach high standing stocks and play a significant role in structuring the top layers of the sediment. However, the behavioral and ecological interactions of foraminifera with the surrounding sediments have been rarely investigated. In order to study these poorly known aspects of foraminiferal ecology, living foraminifera from bathyal and shallower water depths were successfully maintained in microcosms and their relationship with the sediment was investigated. Sedim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 53 publications
3
31
0
Order By: Relevance
“…This led Gross (2002) to suggest that the infaunal/epifaunal dichotomy of foraminiferal microhabitats must be re-examined and Murray (2006) to write that 'the distinction between infaunal and epifaunal [foraminifera] is to some extent arbitrary'. Thus, it cannot at present be suggested whether specialist behaviour favours infaunal or epifaunal species.…”
Section: Discussionmentioning
confidence: 99%
“…This led Gross (2002) to suggest that the infaunal/epifaunal dichotomy of foraminiferal microhabitats must be re-examined and Murray (2006) to write that 'the distinction between infaunal and epifaunal [foraminifera] is to some extent arbitrary'. Thus, it cannot at present be suggested whether specialist behaviour favours infaunal or epifaunal species.…”
Section: Discussionmentioning
confidence: 99%
“…3b), are an important source of environmental heterogeneity in the deep sea, providing habitats and attachment substrates for rich assemblages of other foraminifera and metazoans (Levin and Thomas, 1988;Hughes and Gooday, 2004). Mobile infaunal species bioturbate the sediment as they move through it (Gross, 2002). Conversely, it has been suggested that the pseudopodial systems of foraminifera may help to bind together and stabilize deep-sea sediments (Nyholm, 1957), although this has not yet been clearly demonstrated.…”
Section: Role In Benthic Communitiesmentioning
confidence: 99%
“…Thecate forms, rather than agglutinated or carbonate-secreting forms, likely were the earliest evolving foraminiferal group (16). Thecate foraminifera, which are quite common in the deep sea and shallow Antarctic waters (17)(18)(19), are capable of bioturbating sediments (20).…”
mentioning
confidence: 99%